Low-carbon masonry cementing material as well as preparation method and application thereof

By combining clay waste slag powder with magnesium aluminum silicate slag with clinker for mechanical ball milling, low-carbon masonry gelling materials were prepared, which solved the problem of difficult recycling of clay waste slag powder and magnesium aluminum silicate slag, and achieved the Low-carbon and environmentally friendly masonry materials replace traditional cement.

CN119461899APending Publication Date: 2025-02-18XUYI LANGSHAN CEMENT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411445322.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Materials such as ceramic waste slag powder and magnesium aluminum silicate slag are difficult to effectively recycle and utilize, resulting in secondary pollution of the environment and water resources, and the emissions and costs of harmful gases in the traditional masonry cement production process are high.

Method used

Clay waste slag powder and magnesium aluminum silicate slag are used as raw materials to prepare low-carbon masonry cementitious materials through mechanical ball milling. Combined with the addition of clinker to promote the hydration reaction, artificial stone with excellent mechanical properties is generated.

Benefits of technology

The resource utilization of ceramic waste slag powder and magnesium aluminum silicate slag has been realized, and secondary pollution of the environment and water resources has been avoided. The prepared low-carbon masonry gelling materials have early and long-term strength, strong durability and high water retention rate. , the characteristic of low hydration heat can completely replace traditional masonry cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088335450000071
    Figure BDA0005088335450000071
Patent Text Reader

Abstract

The invention discloses a low-carbon masonry cementing material as well as a preparation method and application thereof. The low-carbon masonry cementing material is prepared from the following raw materials in parts by weight: 95-100 parts of ceramsite waste residue powder, 1-10 parts of magnesium aluminum silicate slag and 0-4 parts of clinker, the low-carbon masonry cementing material contains a large amount of amorphous active silicon, and under the direct excitation hydration action of the magnesium aluminum silicate slag component, the hydration rate of the low-carbon masonry cementing material is promoted, so that the low-carbon masonry cementing material has the characteristics of improved early and long-term strength, strong durability, high water retention rate and small hydration heat; besides, by adding the clinker, mineral components such as CaO, SiO2 and Al2O3 can be released and promoted to be subjected to a hydration reaction, C-S-H series hydrates and ettringite are generated, and the artificial stone is coagulated and hardened into the hard artificial stone at the normal temperature like cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementitious materials, and in particular to a low-carbon masonry cementitious material and a preparation method and application thereof. Background Art

[0002] At present, among China's expanded clay production enterprises, most of the solid waste material resources such as industrial waste sludge, fly ash, etc. have been recycled. However, there is still a considerable amount of industrial expanded clay waste powder discharged from the production of expanded clay that is difficult to recycle, resulting in a large amount of waste of expanded clay waste powder that cannot be effectively recycled and can only be piled up and landfilled, causing secondary pollution to the environment and groundwater resources.

[0003] Magnesium aluminum silicate waste slag is the waste slag discharged from the production of magnesium aluminum silicate products, which is called magnesium aluminum silicate slag. The main component is MgAl 2 SiO 6 , pH value is 8.0-10.0, the shape is white powder, magnesium aluminum silicate slag is mainly piled up and landfilled on farmland, it is difficult to be used in cement clinker production on a large scale and is subject to restrictions.

[0004] Traditional masonry cement is made of silicate cement clinker, which is prepared from natural limestone, clay, mineralizer and coal. It not only emits a large amount of harmful gases into the atmosphere, affecting the environment, but also has high cost. At present, there is no research report on the production of new low-carbon masonry cementitious materials using materials such as ceramsite waste slag powder and magnesium aluminum silicate slag. Therefore, the study of a new low-carbon masonry cementitious material produced using materials such as ceramsite waste slag powder and waste slag magnesium aluminum silicate slag has a positive role in improving the application level of new low-carbon masonry cementitious materials in building materials and promoting the resource utilization of ceramsite waste slag powder discharged from the production of ceramsite enterprises.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a low-carbon masonry cementitious material and a preparation method and application thereof. The present invention uses ceramsite waste slag powder and magnesium aluminum silicate slag as raw materials to process a low-carbon masonry cementitious material, which realizes the resource utilization of ceramsite waste slag powder and magnesium aluminum silicate slag and avoids the secondary pollution of the environment and water resources caused by stacking and landfilling; at the same time, the low-carbon masonry cementitious material prepared by the present invention has excellent mechanical properties and can completely replace the existing traditional masonry cement for use.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The first aspect of the present invention provides a low-carbon masonry cementitious material, wherein the low-carbon masonry cementitious material is made of the following raw materials in parts by weight:

[0009] 95-100 parts of ceramsite waste slag powder, 1-10 parts of magnesium aluminum silicate slag and 0-4 parts of clinker.

[0010] Preferably, the low-carbon masonry cementitious material is made of the following raw materials in parts by weight:

[0011] 95-100 parts of ceramsite waste slag powder, 1-5 parts of magnesium aluminum silicate slag and 2-4 parts of clinker.

[0012] Preferably, the pH value of the ceramsite waste powder is 7.8-8.2.

[0013] Preferably, the pH value of the magnesium aluminum silicate slag is 8.2-8.8.

[0014] Preferably, the pH value of the clinker is 6.5-7.5.

[0015] Preferably, the clinker is low-temperature clinker.

[0016] The second aspect of the present invention provides a method for preparing the low-carbon masonry cementitious material, the method comprising the following steps:

[0017] (a) weighing the raw materials according to weight and mixing them to obtain a mixture;

[0018] (b) The mixture is subjected to mechanical ball milling treatment to a fineness of 1.0% to 1.2%, thereby obtaining the low-carbon masonry cementitious material.

[0019] In the present invention, the fineness of 1.0% to 1.2% means that the particles with a particle size greater than 60 um account for 1.0% to 1.2%.

[0020] The third aspect of the present invention provides an application of the low-carbon masonry cementitious material or the low-carbon masonry cementitious material prepared by the preparation method in the preparation of masonry cement mortar, plastering mortar or cushion concrete construction materials.

[0021] Compared with the prior art, the beneficial effects of the present invention include at least:

[0022] The low-carbon masonry cementitious material of the present invention contains a large amount of amorphous active silicon. Under the direct hydration activation of the magnesium aluminum silicate slag component, the hydration rate of the low-carbon masonry cementitious material is promoted, so that the low-carbon masonry cementitious material has the characteristics of improved early and long-term strength, strong durability, high water retention rate and low hydration heat; in addition, CaO and SiO can be released by adding clinker. 2 、Al 2 O 3 It can also react with other mineral components and promote their hydration reaction to generate CSH series hydrates and ettringite, which can solidify and harden into hard artificial stone at room temperature just like cement.

[0023] The low-carbon masonry cementitious material prepared by physical excitation in the preparation method of the present invention improves the surface energy of the low-carbon masonry cementitious material, increases the specific surface area and internal defects, and can promote the hydration rate of the low-carbon masonry cementitious material. As the hydration process advances, the early and long-term strengths are improved, the durability is good, and the water retention performance is strong. The low-carbon masonry cementitious material is directly used to prepare masonry and plastering mortar, which can reduce the water-cement ratio of the mortar, improve the mortar delamination performance, increase the bonding strength, shorten the mortar setting time, and have good water retention. The mortar will have higher and higher late strength and become a cement mortar hydration crystallization nucleus, so that the prepared mortar has the characteristics of wear resistance, frost resistance, crack resistance, chloride ion resistance and strong carbonization resistance. In addition, the low hydration heat used for cushion concrete can slow down the hydration speed, has high bonding strength, can improve the micro-expansion structure of the concrete interface, reduce internal pores, and improve the chloride ion penetration resistance.

[0024] The low-carbon masonry cementitious material prepared by the invention saves 100% of the limestone, clay, mineralizer and coal used in natural silicate cement clinker and reduces carbon emission by 100%. DETAILED DESCRIPTION

[0025] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0026] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.

[0027] The embodiment of the present invention provides a low-carbon masonry cementitious material, wherein the low-carbon masonry cementitious material is made of the following raw materials in parts by weight:

[0028] 95-100 parts of ceramsite waste slag powder, 1-10 parts of magnesium aluminum silicate slag and 0-4 parts of clinker.

[0029] The low-carbon masonry cementitious material of the present invention contains a large amount of amorphous active silicon. Under the direct hydration activation of the magnesium aluminum silicate slag component, the hydration rate of the low-carbon masonry cementitious material is promoted, so that the low-carbon masonry cementitious material has the characteristics of improved early and long-term strength, strong durability, high water retention rate and low hydration heat; in addition, CaO and SiO can be released by adding clinker. 2 、Al 2 O 3 It can also react with other mineral components and promote their hydration reaction to generate CSH series hydrates and ettringite, which can solidify and harden into hard artificial stone at room temperature just like cement.

[0030] In some embodiments, the low-carbon masonry cementitious material is made of the following raw materials in parts by weight:

[0031] 95-100 parts of ceramsite waste slag powder, 1-5 parts of magnesium aluminum silicate slag and 2-4 parts of clinker.

[0032] By specifically limiting the amount of each raw material, the overall performance of the low-carbon masonry cementitious material can be better improved.

[0033] In some embodiments, the pH value of the ceramsite waste powder is 7.8-8.2.

[0034] In some embodiments, the pH value of the magnesium aluminum silicate slag is 8.2-8.8.

[0035] By limiting the main components of ceramsite waste slag powder and magnesium aluminum silicate slag, the component content in the preparation of low-carbon masonry cementitious materials can be better adjusted, the role of each component can be better promoted, and the performance of the low-carbon masonry cementitious materials can be improved.

[0036] In some embodiments, the pH value of the clinker is 6.5-7.5.

[0037] In some embodiments, the clinker is low-temperature clinker.

[0038] Another embodiment of the present invention provides a method for preparing the low-carbon masonry cementitious material, the method comprising the following steps:

[0039] (a) weighing the raw materials according to weight and mixing them to obtain a mixture;

[0040] (b) The mixture is subjected to mechanical ball milling treatment to a fineness of 1.0% to 1.2%, thereby obtaining the low-carbon masonry cementitious material.

[0041] The low-carbon masonry cementitious material prepared by physical excitation in the preparation method of the present invention improves the surface energy of the low-carbon masonry cementitious material, increases the specific surface area and internal defects, and can promote the hydration rate of the low-carbon masonry cementitious material. As the hydration process advances, the early and long-term strengths are improved, the durability is good, and the water retention performance is strong. The low-carbon masonry cementitious material is directly used to prepare masonry and plastering mortar, which can reduce the water-cement ratio of the mortar, improve the mortar delamination performance, increase the bonding strength, shorten the mortar setting time, and have good water retention. The mortar will have higher and higher late strength and become a cement mortar hydration crystallization nucleus, so that the prepared mortar has the characteristics of wear resistance, frost resistance, crack resistance, chloride ion resistance and strong carbonization resistance. In addition, the low hydration heat used for cushion concrete can slow down the hydration speed, has high bonding strength, can improve the micro-expansion structure of the concrete interface, reduce internal pores, and improve the chloride ion penetration resistance.

[0042] Yet another embodiment of the present invention provides an application of the low-carbon masonry cementitious material or the low-carbon masonry cementitious material prepared by the preparation method in the preparation of masonry cement mortar, plastering mortar or cushion concrete construction materials.

[0043] The low-carbon masonry cementitious material prepared by the invention saves 100% of the limestone, clay, mineralizer and coal used in natural silicate cement clinker and reduces carbon emission by 100%.

[0044] The technical solution of the present invention is further described in detail below through specific embodiments.

[0045] The raw materials used in the following examples are as follows:

[0046] Ceramic slag powder: pH value is 8.1; it comes from the waste residue discharged by the local ceramsite production enterprises in Xuyi County, Jiangsu Province, and is called ceramsite slag powder;

[0047] Magnesium aluminum silicate slag: pH value is 8.5; the waste slag discharged from the production of magnesium aluminum sulfate products by chemical plants in Huai'an City, Jiangsu Province is called magnesium aluminum sulfate slag.

[0048] Low-temperature clinker: pH value is 7.1; sourced from Jiangsu Yancheng Jinni Environmental Protection Technology Co., Ltd.

[0049] Example 1

[0050] This embodiment is a low-carbon masonry cementitious material, which is made of the following raw materials in parts by weight:

[0051] 97 parts of ceramsite waste slag powder and 3 parts of magnesium aluminum silicate slag.

[0052] Preparation method of the above low-carbon masonry cementitious material:

[0053] The preparation method comprises the following steps:

[0054] (a) weighing the raw materials according to weight and mixing them to obtain a mixture;

[0055] (b) The mixture is subjected to mechanical ball milling treatment until the fineness is 1.0%, thereby obtaining the low-carbon masonry cementitious material.

[0056] Example 2

[0057] This embodiment is a low-carbon masonry cementitious material, which is made of the following raw materials in parts by weight:

[0058] 95 parts of ceramsite waste slag powder and 5 parts of magnesium aluminum silicate slag.

[0059] Preparation method of the above low-carbon masonry cementitious material:

[0060] The preparation method comprises the following steps:

[0061] (a) weighing the raw materials according to weight and mixing them to obtain a mixture;

[0062] (b) The mixture is subjected to mechanical ball milling treatment until the fineness is 1.0%, thereby obtaining the low-carbon masonry cementitious material.

[0063] Example 3

[0064] This embodiment is a low-carbon masonry cementitious material, which is made of the following raw materials in parts by weight:

[0065] 95 parts of ceramsite waste slag powder, 3 parts of magnesium aluminum silicate slag and 2 parts of clinker, wherein the clinker is low-temperature clinker with a pH value of 7.1.

[0066] The preparation method of the above-mentioned low-carbon masonry cementitious material:

[0067] The preparation method comprises the following steps:

[0068] (a) weighing the raw materials according to weight and mixing them to obtain a mixture;

[0069] (b) The mixture is subjected to mechanical ball milling treatment until the fineness is 1.0%, thereby obtaining the low-carbon masonry cementitious material.

[0070] Example 4

[0071] This embodiment is a low-carbon masonry cementitious material, which is made of the following raw materials in parts by weight:

[0072] 95 parts of ceramsite waste slag powder, 1 part of magnesium aluminum silicate slag and 4 parts of clinker, wherein the clinker is low-temperature clinker with a pH value of 7.1.

[0073] Preparation method of the above low-carbon masonry cementitious material

[0074] The preparation method comprises the following steps:

[0075] (a) weighing the raw materials according to weight and mixing them to obtain a mixture;

[0076] (b) The mixture is subjected to mechanical ball milling treatment until the fineness is 1.0%, thereby obtaining the low-carbon masonry cementitious material.

[0077] Experimental example

[0078] The low-carbon masonry cementitious materials prepared in Examples 1 to 4 are obtained respectively; and masonry cement (brand: ...) purchased from the market;

[0079] According to the technical requirements for masonry cement in GB / T3183-2017, the low-carbon masonry cementitious materials prepared in Examples 1 to 4 and the masonry cement purchased on the market were tested;

[0080] The test results are shown in Table 1;

[0081] Table 1

[0082]

[0083] From Table 1, we can see that:

[0084] Compared with the masonry cementitious materials on the market, the low-carbon masonry cementitious materials prepared by the embodiments of the present invention have better performance and can completely replace the masonry cement products on the market, thereby realizing the resource utilization of ceramsite waste slag powder and magnesium aluminum silicate slag.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A low-carbon masonry cementitious material, characterized in that: The low-carbon masonry cementitious material is made of the following raw materials in parts by weight: 95-100 parts of ceramsite waste slag powder, 1-10 parts of magnesium aluminum silicate slag and 0-4 parts of clinker.

2. The low-carbon masonry cementitious material according to claim 1, characterized in that: The low-carbon masonry cementitious material is made of the following raw materials in parts by weight: 95-100 parts of ceramsite waste slag powder, 1-5 parts of magnesium aluminum silicate slag and 2-4 parts of clinker.

3. The low-carbon masonry cementitious material according to claim 1 or 2, characterized in that: The pH value of the ceramsite waste slag powder is 7.8-8.

2.

4. The low-carbon masonry cementitious material according to claim 1 or 2, characterized in that: The pH value of the magnesium aluminum silicate slag is 8.2-8.

8.

5. The low-carbon masonry cementitious material according to claim 1 or 2, characterized in that: The pH value of the clinker is 6.5-7.

5.

6. The low-carbon masonry cementitious material according to claim 1 or 2, characterized in that: The clinker is low-temperature clinker.

7. The method for preparing the low-carbon masonry cementitious material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (a) weighing the raw materials according to weight and mixing them to obtain a mixture; (b) The mixture is subjected to mechanical ball milling treatment to a fineness of 1.0% to 1.2%, thereby obtaining the low-carbon masonry cementitious material.

8. Use of the low-carbon masonry cementitious material described in any one of claims 1 to 6 or the low-carbon masonry cementitious material prepared by the preparation method described in claim 7 in the preparation of masonry cement mortar, plastering mortar or cushion concrete construction materials.

Citation Information

Cited By

  • Preparation method of solid cement grinding aid

    CN120965152A